(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Each annual MMTs (Million Metric Tons) are made by Indian Foundry industry, with large opportunities for workers, resulting in national economic development. But industries design and produce vehicle, train, electricity, etc. engineering components. The chemical structure and the presence of its alloying components was primarily determined by the technical properties of grey cast iron. In addition to carbon, silicone is the main alloy that helps graphite forming and decreases shrinking. During solidification processes the cast iron properties may be improved by chilling. Chilling encourages directional strengthening The thesis on Cast iron that mentioned, Cast iron types, Grey Cast iron types, Role of elements alloy, Combination with the use of chills and alloys, Chill, chill kinds, Ductile chilled iron cast, Cast iron mechanical characteristics, Cast iron tensile characteristics, Cast iron toughness